Questions   
Sort: 
 #9
avatar+12530 
+1
Apr 27, 2020
 #1
avatar+23248 
+1

                                                                                                                            2x2 - 11x + 14  =  0

Move the constant term to the other side:                                                             2x2 - 11x        =  -14

Divide all terms by the coefficient of the x2-term:                                                 x2 - (11/2)x      =  -7

Complete the square by

  1)  dividing the coefficient of the x-term by 2:  (-11/2) / 2  =  -11/4

  2)  squaring that number:  (-11/4)2  =  121/16

  3)  adding this term to both sides of the equation:                                   x2 - (11/2)x + 121/16  =  -7 + 121/16 

Factor and combine numbers:                                                                                    (x - 11/4)2  =  9/16

Find the square root of both sides:                                                                                 x - 11/4   =   +/- 3/4

Finish:                  x - 11/4  =  3/4            x - 11/4  =  -3/4

                                      x  =  14/4                     x  =  8/4  

                                      x  =  7/2                       x  =  2

Apr 27, 2020

2 Online Users